2023
DOI: 10.1039/d2na00724j
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-doped copper vanadate: a dual active electrocatalyst propelling efficient H2 evolution and glycerol oxidation in alkaline water

Abstract: Strategically doped metal oxide nanomaterials signify a rapidly growing genre of functional materials with a wide range of practical applications. Copper vanadate (CuV) represents one such highly active system, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In other words, the appearance of these four peaks demonstrates that Ce 3+ center is indeed present . Also, the core spectrum of V 2p deconvolutes into two peaks at 524.4 and 517.1 eV, which designates the V 2p 1/2 and V 2p 3/2 states, respectively (Figure k) . High-resolution O 1s signal deconvolution suggests the presence of two peaks at 531.7 and 529.6 eV (Figure l).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In other words, the appearance of these four peaks demonstrates that Ce 3+ center is indeed present . Also, the core spectrum of V 2p deconvolutes into two peaks at 524.4 and 517.1 eV, which designates the V 2p 1/2 and V 2p 3/2 states, respectively (Figure k) . High-resolution O 1s signal deconvolution suggests the presence of two peaks at 531.7 and 529.6 eV (Figure l).…”
Section: Resultsmentioning
confidence: 91%
“…59 Also, the core spectrum of V 2p deconvolutes into two peaks at 524.4 and 517.1 eV, which designates the V 2p 1/2 and V 2p 3/2 states, respectively (Figure 2k). 60 High-resolution O 1s signal deconvolution suggests the presence of two peaks at 531.7 and 529.6 eV (Figure 2l). The peak at 530.7 eV corresponds to the existence of surface lattice oxygen; in contrast, the presence of OH groups on the surface of CeVO 4 is indicated by the peak at 528.6 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…181 Doping with Co( ii ) in monoclinic Cu 2 V 2 O 7 (Co 5% –CuV, Co 10% –CuV, and Co 20% –CuV), when examined for EC GOR, exhibited an overpotential of 160 mV to reach a current density of 10 mA cm −2 and a faradaic efficiency of >90% in 1 M KOH electrolyte. 182 Porous Cu/Cu 2 O films were doped with Ni 2+ and Cl − , resulting in a change in morphology and 3-fold enhancement of ECSA with concurrent improved GOR kinetics. 183 Recently, Bai et al reported electrocatalytic N 2 reduction, simultaneously replacing EC OER with EC GOR at the anodic part by bimetallic RhCu-ultrathin nanoflake nanoaggregates (RhCu-BUNNs).…”
Section: Electrocatalytic Valorization Of Glycerolmentioning
confidence: 99%
“…First-principles calculations reveal that CuO and NaHCO 3 increase electrophilicity of C 2 -C 3 and results in direct cleavage of C-C bond, while in NaOH, the removal of H from C 2 of GLAD intermediate followed by dehydration leads to lactic acid production 181. Doping with Co(II) in monoclinic Cu 2 V 2 O 7 (Co 5% -CuV, Co 10% -CuV, and Co 20% -CuV), when examined for EC GOR, exhibited an overpotential of 160 mV to reach a current density of 10 mA cm −2 and a faradaic efficiency of >90% in 1 M KOH electrolyte 182. Porous Cu/Cu 2 O films were doped with Ni 2+ and Cl − , resulting in a change in morphology and 3-fold enhancement of ECSA with concurrent improved GOR kinetics 183.…”
mentioning
confidence: 99%
“…20−23 However, the selective oxidation of glycerol to one of the many possible C3−C1 products is a major issue. 4,9,23 Therefore, the development of alternate catalytic systems to achieve the selective and efficient oxidation of glycerol to FA is highly desirable.…”
Section: ■ Introductionmentioning
confidence: 99%